PENGARUH LABEL HALAL DAN INFORMASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN COKLAT CADBURY DAIRY MILK (STUDI KASUS PASCA TERDAPAT ISU DNA BABI (PORCINE)) - admin, Sri Devie Melavanic B11111080 (Jurnal Manajemen Update, 2016)
This research intends to find out the effect of Halal Label and Product Information toward Purchasing Decision on Cadbury Dairy Milk Chocolate post the issue of Pig DNA (Porcine) in its ingredients. This research designed as a descriptive statistic research. The sampling technique used in this research is purposive sampling technique with a total sample of 100 respondents. The population of this research is the whole students of the faculty of Economics of Tanjungpura University Pontianak. The Technique of Analysis that utilized in this research is multiple linear regression analysis. The concluded that Halal Label and Product Information indicated positive and significant effect toward the purchasing decision on Cadbury Dairy Milk Chocolate Post Pig DNA (Porcine) issue. Keyword: Halal Label, Product Information, Purchasing Decision, Pig DNA